A Review on Study on Osteoporosis and Impact of Drugs for its Management - Dhoot, Indra Kuamr; singh, Charanjeet (Journal of Drug Delivery and Therapeutics, 2019)
Osteoporosis is characterized by low bone mineral density (BMD) and loss of the structural and biomechanical properties that are required to maintain bone homeostasis. Physicians are knowledgeable about the association of osteoporosis with aging, postmenopausal status, and secondary causes, including chronic illnesses or lifestyle issues that promote osteoporosis. Building strong and healthy bones requires an adequate dietary intake of calcium beginning in childhood and adolescence for both sexes. Most importantly, however, a high dietary calcium intake or taking calcium supplements alone is not sufficient in treating osteoporosis and should not be viewed as an alternative to or substituted for more potent prescription medications for osteoporosis. Keywords: BMD, Osteoporosis, calcium supplements, skeletal disease.